EFFECT OF MUTAGENESIS ON GROWTH AND YIELD RELATED TRAITS IN BLACKGRAM (Vigna mungo (L.) Hepper) - M. SREEVALLI DEVI *, D. MOHAN REDDY, V.L.N. REDDY, D. LOKANADHA REDDY, P. SUDHAKAR; S. SOFIA (The Journal of Research ANGRAU, 2021)
The investigation was conducted to understand the immediate effect of mutagenesis on growth and yield traits in blackgram in order to select most effective mutagen and its dose/concentration which induce desired improvement without disturbing the better attributes. The seeds of two varieties of blackgram viz., LBG 752 and TBG 104 were treated with gamma rays (200 Gy, 300 Gy, 400 Gy, 500Gy and 600 Gy), EMS (Ethyl Methane Sulphonate) (0.2%, 0.3%, 0.4%, 0.5% and 0.6%) and MH (Maleic Hydrazide) (0.01%, 0.02% and 0.03%). The observations were recorded on seed germination, shoot length and root length under in-vitro condition and seedling emergence, seedling survival, seedling height, pollen fertility, plant height, number of primary branches per plant, number of clusters per plant, number of pods per plant, number of seeds per pod, pod length, seed fertility, 100-seed weight and seed yield per plant under field condition. Higher doses of all the mutagens caused considerable reduction in all the traits studied. MH treatment resulted in drastic reduction in seedling characters viz., seedling emergence, seedling survival and seedling height followed by EMS and gamma rays treatment. Based upon the sensitivity of mutagen, gamma rays were highly effective for modifying majority of the traits in the crop with less biological damage followed by EMS and MH treatments. Both the parental varieties differed themselves for mutagen treatments. The reduction in the traits with increasing dose of mutagens was more prominent in LBG 752 than TBG 104 indicated that LBG 752 was more sensitive to mutagen treatment. These findings would greatly help for cost effective selection of mutagen and variety for successful generation of variation in mutation breeding programmes aimed at blackgram crop improvement.